THE USE OF LINE WEBTOON COMIC STRIPS TO UPGRADE STUDENTS’ VOCABULARY MASTERY - Luh Putri Maharani (Yavana Bhasha : Journal of English Language Education, 2021)
Vocabulary is the key for the learners’ language change in learning as a foreign languageincluding English. However, Indonesian students still have problems in vocabulary building,particularly to memorize meaning of new words. This fact implies that they need effective ways tolearn vocabulary. It would be more beneficial to use an effective vocabulary teaching technique to helpthe students in upgrading their vocabulary mastery. The use of relevant media in teaching vocabularywill also boost student’s motivation. The aim of this study was to reveal how Line Webtoon comic canbe used to teach vocabulary, the student’s vocabulary mastery, and the student’s responses toward theuse of Webtoon comic. The participants in this study were ninth-grade students and their Englishteacher. This research applied qualitative design. The data was gathered through observation duringonline learning in Google Classroom, student’s task and the interview process. Based on the data, theprocess of using Line Webtoon for ninth graders was successfully upgraded the students’ vocabularymastery and motivation to read through online comic. It also showed that the students were interestedto read because Webtoon consisted of many pictures and they were able to get many new words byusing online media.